Calcium‐Channel Blockers Attenuate the Antiplatelet Effect of Clopidogrel. Issue 5 (October 2015) - Gremmel, Thomas; Durstberger, Markus; Eichelberger, Beate; Koppensteiner, Renate; Panzer, Simon
Summary Aims Dihydropyridine calcium‐channel blockers (CCBs) inhibit cytochrome 3A4 and could therefore interfere with the conversion of clopidogrel to its active form. The impact of CCBs on the antiplatelet effect of clopidogrel has not been studied with assays directly capturing platelet activation to adenosine diphosphate (ADP), so far. We therefore sought to investigate platelet activation in response to ADP by flow cytometry in clopidogrel‐treated patients without and with CCBs. Methods Platelet surface P‐selectin expression and activated glycoprotein (GP) IIb/IIIa in response to ADP were determined by flow cytometry in 302 patients on dual antiplatelet therapy with aspirin and clopidogrel after successful angioplasty with stent implantation. Results Ninety‐two patients (30.5%) received CCBs. Patients with concomitant CCB therapy showed significantly higher platelet surface expressions of P‐selectin and activated GPIIb/IIIa in response to ADP than patients without CCBs (both P ≤ 0.03). Moreover, the fold increase of P‐selectin and activated GPIIb/IIIa in response to ADP was significantly more pronounced in patients taking CCBs (both P ≤ 0.03). The associations of ADP‐inducible activated GPIIb/IIIa and fold increase of activated GPIIb/IIIa after the addition of ADP with CCB therapy remained significant after adjustment for differences in patient characteristics and factors that were previously associated with clopidogrel response by multivariate regression analyses (both P < 0.05). High levels of ADP‐inducible P‐selectin and activated GPIIb/IIIa were seen significantly more frequent in patients with CCBs than in patients without CCB therapy (both P ≤ 0.01). Conclusion Dihydropyridine CCBs attenuate the effect of clopidogrel on ADP‐inducible platelet activation in patients undergoing angioplasty and stenting for cardiovascular disease.